Public Health, Socioeconomic Responses, and associated Challenges against Coronavirus Disease 2019 Pandemic in Nigeria - Abdullahi, Idris Nasir; Emeribe, Anthony Uchenna; Ghamba , Peter Elisha; Sani, Musa (Open Access Macedonian Journal of Medical Sciences, 2020)
For over 6 months of its emergence, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of coronavirus disease 2019 (COVID-19) pandemic, has resulted to unprecedented global health challenge and economic uncertainties. The pandemic swiftly disseminated to almost all the countries and territories of the world. The index case in Nigeria was imported by an Italian citizen on February 27, 2020. Typical of a novel respiratory tract viral infection, the spread of SARS-CoV-2 in Nigeria was slow in the first few days. However, as at 8:00 AM GMT+1, July 1, 2020, there were 25694 confirmed COVID-19 cases. With the continuous daily rise in the incidence of SARS-CoV-2 infection, enhanced surveillance programs were immediately activated and implemented in all parts of Nigeria. Even though an inadequate number of persons have been tested so far, the government of Nigeria has been activating public health laboratories to scale up its testing capacity. Due to the impact of partial lockdown and curfew in most states of Nigeria, the government has been able to provide some form of palliatives to vulnerable populations. This study aims to review and present the various public health and socioeconomic responses and challenges of the COVID19 pandemic in Nigeria. This reflects the efforts and successful steps taken to minimize the spread of COVID-19 in Nigeria.